Psychometric properties of the Academic Self-Concept Scale in Chilean university students - Méndez Vera, Juan (2018)
The current study aimed to evaluate the psychometric properties of the Academic Self-Concept Scale in a sample of university students from Chile. To that end, a cross-sectional study was conducted and participants were selected through a probabilistic hierarchical method, resulting in a sample size of 1290 students of both genders (57% females and 43% males) with a mean age of 21.03 years. The structure of the scale was checked through an exploratory and confirmatory factor analysis using the cross-sample method. The analysis of the scale showed suitable psychometric properties to be used in university students, while maintaining its two-factor structure that explain 53.7% of the construct ́s variance. Cronbach’s Alpha and McDonald’s Omega regarding the Perceived Performance subscale were α = .753 and ω = .787, and regarding the Academic Self-Efficacy subscale were α = .802 and ω = .867. The results enable us to conclude that the Academic Self-Concept Scale is a valid and reliable instrument to assess academic self-concept in university students.